Penerapan dan Pelatihan Sistem Pembayaran Sekolah di SMK Brahari sebagai Upaya Transformasi Layanan Keuangan Sekolah - Ismasari Nawangsih; Tri Ngudi Wiyatno; Edy Widodo; Eko Budiarto; Annisa Maulana Majid (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Digital transformation in the education sector demands increased efficiency and transparency in school financial management. However, many schools, including SMK Brahari, still rely on manual payment systems that are prone to errors and lack transparency. The identified gap is the absence of an integrated and user-friendly digital payment system accessible to all stakeholders. This community service activity aimed to implement and provide training on a digital school payment system for 20 administrative and educational staff. The methods included initial observation, development of a simple system, hands-on training, and implementation assistance. Evaluation results showed that 85% of participants understood the system workflow, 90% found it helpful in simplifying their tasks, and all participants expressed readiness to implement it. The system proved effective in improving efficiency, transparency, and ease of payment monitoring, marking an important step toward transforming school financial services.